AKTIVITAS ANTIOKSIDAN EKSTRAK JAHE MERAH (Zingiber officinale var. rubrum) MENGHAMBAT OKSIDASI MINYAK KACANG TANAH (Arachis hypogaea L.) - Junedi Saragih; Jan Assa; Tineke M. Langi (Universitas Sam Ratulangi, 2015)
ABSTRACT Â Red Ginger is a spice-containing compounds - natural antioxidant compounds. This study aims to determine the antioxidant activity of ethanol extract red ginger in inhibiting the oxidation of peanut oil. This study uses a completely randomized design (CRD) with the addition of the ethanol extract treatment red ginger. Each treatment with 4 levels of concentration: 0%, 0.05%, 0.1%, and 0.15% with repeat three times. The ethanol extract red ginger added to the peanut oil and incubated at 60Â°C for 72 hours. Laboratory analyzes performed every 24 hours. The results showed that the yield of ethanol extract red ginger produced in this study was 6.78%. The ethanol extract red ginger has antioxidant activity inhibiting oxidation of peanut oil, it can be seen from the figures peroxide controls (without extract) treatment with the addition of red ginger extract. The higher concentration of ethanol extract of the stronger activity inhibiting the oxidation of peanut oil. Â Keywords: Antioxidant, ethanol extract, red ginger, peroxide values, Incubation